Cirque du Freak. Volume 5, Trials of death - Shan, Darren (Yen Press, 2010)
A manga adaptation of the fifth book in the Cirque du Freak series in which Darren begins the Trials of Initiation to prove himself worthy of being a half-vampire, even as the clan's blood foes, the vampaneze, gather near Vampire Mountain.